Post-Privatisation Ownership Structure and Productivity in Russian Industrial Enterprises - John S. Earle (Fondazione Eni Enrico Mattei (FEEM), 1999)
This paper investigates the impact of ownership structure on the productivity performance of Russian industrial enterprises. The analysis compares the effects of several types of new private owners - insiders (managers and other employees) and outsiders (individual and institutional investors) - with continued ownership by the state, and it takes into account possible selection effects in the privatisation process that may bias the observed ownership-performance relationship. The results provide some evidence that ownership change in Russia was already having some positive effects, shortly after the conclusion of the voucher privatisation process, but that those effects were strongest in companies with concentrated outside owners. Because the design of the Russian privatisation programme appears to have been biased against such institutional investors, the latter finding only emerges after a careful analysis of the simultaneous determination of ownership and performance through the privatisation process.
Keywords: G3; G32; L33; 330; Ownership Structure; Productivity; Russian industrial enterprise; Eigentümerstruktur; Produktivität; Privatisierung; Schätzung; Russland